A consistency-driven particle-advection formulation for weakly-compressible smoothed particle hydrodynamics. (15th November 2021) - Zhu, Yujie; Zhang, Chi; Hu, Xiangyu
Abstract: The traditional smoothed particle hydrodynamics is not 0th-order consistent and suffers from tensile instability which induces void regions when negative pressure presents in the flow. In order to improve the consistency and stability of the method, we propose a consistency-driven particle-advection formulation, which regularizes the particle configuration by local particle consistency instead of using background pressure. With the target of the normalization condition, the modification of particles position can be evaluated by gradient descent method according to the error between unity and the integral of kernel. In addition, the error term is modified to be negative to further improve the effectiveness and avoid the attraction between each pair particles. Note that in present formulation no physical-related parameter is introduced. A number of challenging test cases including lid-driven cavity, taylor-green vortex and fluid–structure interactions are investigated to validate the accuracy and robustness of the present method. Highlights: A new consistency-driven particle-advection formulation for WCSPH is presented. The present formulation eliminates the tensile instability of WCSPH method. Versatility of present method is demonstrated in simulations of FSI benchmarks.